Front cover: Bottom‐up proteomics of envelope proteins extracted from spinach chloroplast via high organic content CE‐MS. Issue 5 (9th March 2020) - Cheng, Jianhui; Morin, Gregg B.; Chen, David D. Y.
Abstract : DOI: 10.1002/elps.201900452 The cover picture shows a newly developed high‐organic‐content capillary electrophoresis‐tandem mass spectrometry (HOCE‐MS/MS) method for the proteomic analysis of envelope proteins extracted from spinach leaves. The use of up to 70% methanol in the background electrolyte improve the performance of CE‐MS bottom‐up analysis of membrane proteins containing more hydrophobic peptides. The result is comparable with a nano‐LC system with only one‐sixth of the sample consumption.